2011
DOI: 10.1182/blood-2010-11-316521
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and break of immune tolerance against human factor VIII in a new transgenic hemophilic mouse model

Abstract: Replacement of the missing factor VIII (FVIII) is the current standard of care for patients with hemophilia A. However, the short half-life of FVIII makes frequent treatment necessary. Current efforts focus on the development of longer-acting FVIII concentrates by introducing chemical and genetic modifications to the protein. Any modification of the FVIII protein, however, risks increasing its immunogenic potential to induce neutralizing antibodies (FVIII inhibitors), and this is one of the major complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Moreover, studies performed in hemophilic mice, rats and rabbits showed a lower incidence of anti-FVIII antibodies in animals infused with PEGylated FVIII than in those infused with its recombinant non-PEGylated counterpart. On the other hand, a recent report by van Helden et al [48] indicated that PEGylation of FVIII could also result in an FVIII protein that expresses higher immunogenicity in hemophilic mouse models. Also, incorporation of PEGylated lipids into complexes of FVIII and phosphatidylinositol resulted in increased immunogenicity following intravenous infusion in a murine hemophilia A model [49].…”
Section: On the Immunogenicity Of Bio-engineered Fviii Derivativesmentioning
confidence: 99%
“…Moreover, studies performed in hemophilic mice, rats and rabbits showed a lower incidence of anti-FVIII antibodies in animals infused with PEGylated FVIII than in those infused with its recombinant non-PEGylated counterpart. On the other hand, a recent report by van Helden et al [48] indicated that PEGylation of FVIII could also result in an FVIII protein that expresses higher immunogenicity in hemophilic mouse models. Also, incorporation of PEGylated lipids into complexes of FVIII and phosphatidylinositol resulted in increased immunogenicity following intravenous infusion in a murine hemophilia A model [49].…”
Section: On the Immunogenicity Of Bio-engineered Fviii Derivativesmentioning
confidence: 99%
“…34 The expression of hFVIII is liver specific since it is directed by the murine albumin enhancer/promoter. While a transgenic line had detectable hFVIII mRNA but no detectable hFVIII protein in the circulation, the mice were immunologically tolerant to hFVIII upon challenge with recombinant hFVIII.…”
Section: The Hemophilia a Micementioning
confidence: 99%
“…In the second humanized haemophilic mouse model, a human FVIII cDNA transgene, regulated by the liver‐specific albumin promoter, has been microinjected into fertilized oocytes, and founder mice were crossed with exon 17 knockout haemophilia A mice . Despite the fact that FVIII mRNA can be found in several tissues in these mice (including liver, brain and gonads), they do not express FVIII in their plasma.…”
Section: Factor VIII Inhibitors: Lessons From Animal Models – David Lmentioning
confidence: 99%